URGENCY REKAM MEDIK BAGI DOKTER PRAKTEK BERDASARKAN UNDANG â€“UNDANG NOMOR 29 TAHUN 2004 TENTANG PRAKTEK KEDOKTERAN - Wilda Masnianti; Dr. Eddy Asnawi; Dr. H. Bahrun Azmi (Jurnal Ilmiah Advokasi, 2022)
Medical records are social data, health demographic data and the results of post-examination doctor diagnoses and complaints faced by patients. So that accuracy, thoroughness and confidentiality become the basis for storing patient data considering the responsibility for medical records. Problems that often arise in the world of health cannot be separated from medical malpractice. Both doctors and hospitals or clinics in defending the operational standards set out in the medical code of ethics usually use medical records as legal evidence in law enforcement processes, medical and dental disciplines as well as medical ethics and dental ethics enforcement. the doctor is a healthy person who is also an expert in the field of disease, while the patient is a sick person who is layman about his illness. In Law Number 29 of 2004 concerning Medical Practices, the explanation of Article 46 paragraph (1), what is meant by medical records are files containing notes and documents regarding patient identities, examinations, treatment, actions and other services that have been provided to patients. Because of their ignorance, the patient submits the problem or illness he is suffering to to the doctor for his recovery. The doctor-patient relationship, legally, generally occurs through an agreement or contract. Starting with a question and answer (anamnesis) between the doctor and patient, then followed by a physical examination, finally establishing a diagnosis.Â Keywords: Doctor, Patient, Hospital